Optimization of Ni-Co-metallic-glass powder (Ni60Cr10Ta10P16B4) (MGP) nanocomposite coatings for direct methanol fuel cell (DMFC) applications. (29th March 2023) - Boostani, Najmeh; Vardak, Shirin; Amini, Rasool; Mohammadifard, Zahra
Abstract: In this research, a novel Ni-Co-metallic glass composite was fabricated and the effect of the co-deposition of Ni60 Cr10 Ta10 P16 B4 amorphous metallic glass powder (MGP) on the morphology and electrocatalytic properties of Ni–Co coatings was evaluated. The process was initiated by producing Ni60 Cr10 Ta10 P16 B4 via mechanical alloying of elemental powders using a planetary ball mill. Then, Ni–Co nanocomposite coatings were deposited on a copper substrate by the addition of different amounts of MGP via the electrodeposition method in a Watts bath. Then, the microstructure and chemical composition of the deposits were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS) successively. The electrocatalytic performance of the coatings was evaluated in a methanol-containing alkaline (1 M NaOH) solution through cyclic voltammetry (CV). The enhancement of the electrocatalytic activity of Ni–Co coating through the co-deposition of MGP was observed. It was also concluded that the electrocatalytic properties of composite coatings are optimized when 7.5 g L −1 of MGP is added to the electroplating bath. Moreover, MGP was demonstrated to have altered the microstructure and the content of Co besides enhancing the roughness and specific surface of coatings. Graphical abstract: Image 1 Highlights: Fabrication of a novel Ni–Co nanocomposite coating with MGP. Evaluation the effect of MGP on electroanalytical properties. A sharp increase in the peak current (5.8 to 17.1 mA cm −2 ) by deposition of MGP. A transition from FCC to HCP lattice by co-deposition of MGP. A reduction in peak potential by co-deposition of MGP.